Types of Lexical Transformations in Closely Related Literary Translation (Linguostylistic Studies, 2016)
The article is devoted to a detailed description of the possible translation (cross-language) transformations that occur in inter-Slavic translations, the specificity of which is based on deep genetic relationship between source and target languages. Such types of lexical transformations as encoding, lexical-semantic substitutions, lexical-stylistic replacement and explication have been analyzed in the context of the problem under discussion. The research has been done on the materials of Mykhailo Stelmakh’s stories «The Geese are Flying» and «The Holy Supper» since the examples are rather illustrative. Key words: Ukrainian-Russian translation, lexical transformation, transcription, transliteration, lexical-semantic substitution, lexical-stylistic replacement, descriptive and approximate translation. References